CONTROLLED HYPERTENSION: THE EFFICACY OF PAPAYA JUICE IN LOWERING HIGH BLOOD PRESSURE IN THE ELDERLY - Bili, Maria; Damatasia, Wira; Suroso, Heri; Sulaksono, Ari Dwi (SYNTHESIS Global Health Journal, 2024)
Background. Reducing blood pressure in the elderly can be achieved through the utilization of alternative treatments, one of which is papaya juice. Hypertension in the elderly is highly perilous and can lead to fatal consequences. This research aimed to investigate the efficacy of papaya juice consumption in lowering blood pressure among the elderly population. Research Method. This research employed a Quasi-Experimental design with a Pretest-Posttest Control Group Design. The population studied consisted of all hypertensive patients at the Mojolangu Community Health Center. Sampling was conducted using a purposive sampling technique, with a total of 30 respondents – 15 assigned to the control group and 15 to the intervention group. Data collection utilized measurement tools including a Sphygmomanometer, stethoscope, and observation sheets. Data analysis was performed using Wilcoxon and Mann-Whitney tests. Findings. "The results of the study using the Wilcoxon test revealed that the systolic blood pressure had a p-value of 0.000 (<0.05), and for diastolic blood pressure in the intervention group, a p-value of 0.000 (<0.05) was obtained. This indicates that papaya juice is effective in assisting with blood pressure reduction. Further assessment of the difference in systolic and diastolic blood pressure reduction was conducted through the Mann-Whitney test, yielding a p-value of 0.049, indicating a significant difference. Conclusion.  Papaya mengkal juice is highly effective and can be considered a viable alternative non-pharmacological therapy option to aid in lowering blood pressure in elderly individuals with hypertension.